Use of a Mandibular Plate to Maintain Intergonial Width in a Partially Edentulous Patient Undergoing Mandibular Symphysis Reconstruction. Issue 4 (December 2013) - Susarla, Srinivas; Gordon, Paul E.; Attarpour, Ali R.; Winograd, Jonathan M.; Peacock, Zachary S.
One of the most challenging and essential aspects of management of patients with traumatic or ablative deformities involving the mandibular symphysis is maintenance of intergonial width. Classically, the use of occlusal splints has been a simple and cost-effective solution to this problem. Patients who are edentulous, the use of Gunning splints with circummandibular wires is an alternative strategy. In the present report, we describe the use of a mandibular fixation plate for maintenance of intergonial width in an edentulous patient with a postablative mandibular symphysis defect.